Outage Probability of Dual-Hop CSI-assisted Relay Systems over Rayleigh/Nakagami-m Fading Channels with Interferences at the Relay - Cvetkovic, A. M.; Stefanovic, M. C. (Elektronika ir Elektrotechnika, 2012)
This paper studies the performance of a dual-hop amplify-and-forward system where the source-relay and the relay-destination channels experience Rayleigh and Nakagami-m fading, respectively. The relay node is corrupted by Nakagami-m faded multiple co-channel interferences while destination node is perturbed by only an additive white Gaussian noise. New closed-form expression for the outage probability of the end-to-end signal-to-interference and noise ratio (SINR) is derived for integer value of fading parameter on the second hop. The results of this paper show influence of the outage threshold, co-channel interferers and various values of fading parameter on the system performance. Numerical results obtained by analytical approach are verified by Monte Carlo simulations. Ill. 4, bibl. 10 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.122.6.1830